Placenta Accreta Spectrum Disorder in a Patient with Six Previous Caesarean Deliveries: Step by Step Management - Gloria Calagna; Salvatore Polito; Francesco Labate; Rosa Anna Guiglia; Francesca De Maria; Chiara Bisso; Gaspare Cucinella; Giuseppe Calì (Case Reports in Obstetrics and Gynecology)
The definition placenta accreta spectrum disorders (PAS) introduced by FIGO (International Federation of Gynaecology and Obstetrics) indicates an abnormal, pathological adherence or invasion of the placenta. The growing worldwide incidence of this pathological entity, and the possible serious correlated surgical risks, has caused a significant increase in attention among the scientific community. Previous caesarean delivery and presence of placenta previa are the main risk factors for the onset of PAS. Here, we present the intriguing case of a 39-year-old woman, at the 33rd week of gestation, with six previous caesarean sections and with a diagnosis of placenta previa accreta. At our referral center for PAS disorders, we successfully managed this difficult case with the help of a multidisciplinary skilled team.